Efficacy of reciprocating and ultrasonic activation of 6% sodium hypochlorite in the reduction of microbial content and virulence factors in teeth with primary endodontic infection. (28th January 2020) - Aveiro, E.; Chiarelli‐Neto, V. M.; de‐Jesus‐Soares, A.; Zaia, A. A.; Ferraz, C. C. R.; Almeida, J. F. A.; Marciano, M. A.; Feres, M.; Gomes, B. P. F. A.
Abstract: Aim: To evaluate in a clinical trial the efficacy of reciprocating and ultrasonic activation of 6% sodium hypochlorite (NaOCl) in the microbial composition and reduction in microbial load as well as in levels of lipopolysaccharide (LPS) and lipoteichoic acid (LTA) in teeth with primary endodontic infections. Methodology: Samples were collected from 24 root canals with pulp necrosis and periapical lesions, before and after chemo‐mechanical canal preparation. The teeth were randomly divided according to the activation protocol as follows: control group without activation (WA, n  = 8), reciprocating activation group using Easy Clean tip (EC, n  = 8) and ultrasonic activation group using Irrisonic insert (US, n  = 8). Microbiological specimens were processed using a culture technique and microbiota composition was analysed using the checkerboard technique. The levels of LPS and LTA were quantified using limulus amebocyte lysate (LAL) and enzyme‐linked immunosorbent assay (ELISA), respectively. The Fisher's exact test, Kruskal–Wallis, Dunn's and Wilcoxon's test with a significance level of P  < 0.05 were used for statistical analysis. Results: All initial specimens had growth of viable bacteria in fastidious anaerobe agar (FAA), with an average of 10 5  CFU mL −1, whereas only one case had such growth after chemo‐mechanical canal preparation. LPS and LTA were recovered in 100% of the cases. Chemo‐mechanical canal preparation significantly decreased the levels of LPS and LTA ( P  < 0.05), but no significant differences were found between the groups ( P  > 0.05). Through the checkerboard technique, bacteria were found in 100% of the initial specimens with concentrations between <10 5 and 10 6 . The most frequently identified microorganisms were Prevotella nigrescens and Enterococcus hirae . After chemo‐mechanical canal preparation, many species were not detected in any of the three groups tested. A significant reduction occurred in Group US, followed by Groups EC and WA. Conclusions: Activation of 6% NaOCl reduced the levels of LPS and LTA with no differences between the groups. However, ultrasonic activation was associated with a greater reduction in microbial load within root canals.